Menuju Kampung Bersinar dengan Pelatihan Kreasi Tanaman Hias bagi Ibu-Ibu PKK di Kelurahan Gadang Kota Malang - Setiyowati, Ernaning; Junara, Nunik; Kurniawaty, Prima (JRCE (Journal of Research on Community Engagement), 2020)
Malang City has an annual program of activities for villages namely Kampung Bersinar (Clean, Healthy, Beautiful, Beautiful and Neat). One of the areas that have greening problems is RW 04, Gadang, Malang City on the banks of the Brantas river. Lack of greening in this area causes this area to be prone to landslides because the area is very contoured. That's why the focus of community service is to educate the public in the field of greening to improve the quality of the environment in the area. The method used is Participatory Action Research (PAR) which involves community action in its activities. The activity carried out was to train the creation of ornamental plants in the form of spheres growing to PKK women in RW 04, Gadang, Malang. The results of this activity are PKK mothers who have new knowledge by making ornamental plant creations that can be applied in the area so that it will improve the quality of the green environment in the area..